The Effect of Tactical Skills Exercises On Ball Possession and Total Points Scored for Youth Basketball Players Aged 18 Years Old - Jaber, Hashem; Saleh, Salwan (Journal of Physical Education, 2020)
The research aimed at design exercises for offense tactical skills to identify the development in ball possession and total points scored during these exercises. In addition to that, the research aimed at identifying the level of development of these exercises. The researchers used the experimental method on (20) youth basketball players aged 18 years old divided into two groups experimental and controlling groups.  Many matches were conducted; five formal pre matches and five formal post matches. The data was collected and treated using SPSS to conclude that there is a positive development in ball possession and total points scored during matches.